The Role of School Administration in Enhancing Effectiveness of Guidance and Counseling Services in Cameroon Secondary Schools - Asongwe Cyprian Foche, Dr (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study sets out examine the role of school administration in enhancing effectiveness of guidance and counseling services in Cameroon secondary schools. The effectiveness of guidance and counseling services cannot be underestimated as it significantly contributes to the overall internal effectiveness of the school system as a whole. This means that the school administrator has a lot to contribute in ensuring the effectiveness of this service. This study adopted the research survey design and the main instrument for data collection was the questionnaire. The study used a simple random sampling technique to select 223 secondary schools from the centre regions of Cameroon. The data was analyzed using the Kendal tau formula and the following results were obtained per hypothesis. In the first hypothesis we found that School administrators’ leadership style significantly affects the effectiveness of guidance and counseling services by 36.4% (p.value 0.00 ˂0.05; r=0.364) in the first hypothesis. In the second hypothesis, the Allocation of Resources significantly influences the effectiveness of guidance and counseling services by 35.5% (p.value 0.00 ˂0.05; r=0.355); while in the third hypothesis Principal’s communication influences the effectiveness of guidance and counseling services by 32.3% (p.value 0.00 ˂0.05; r=0.323). Based on these findings it can be concluded that the role of school administration is significant in enhancing effectiveness of guidance and counseling services in Cameroon secondary schools. Recommendations were made to stakeholders concerned.